Molecular simulations of ultra-low-energy nitrogen ion bombardment of A-DNA in vacuum - Ngaojampa,C. (Elsevier Inc., 2015)
For investigating mechanisms involved in low-energy ion beam induced mutation, besides experiments using low-energy and low-fluence ions to bombard naked DNA, molecular simulations were carried out as an effort towards the insight in molecular interactions between ions and DNA. In the current study, Monte Carlo (MC) and molecular dynamics (MD) simulations were applied. The results of MC simulations provide some clues about the interaction energies and sites of preference of N-ion bombardment on an A-DNA short duplex strand. MD simulations of a single N-ion moving towards the same DNA strand with different linear velocities corresponding to bombardment energies of 0.1, 1, 10 and 100 eV revealed information about changes in bond lengths and visibly distorted structures of bombarded nucleotides. The simulations demonstrated that ion-bombardment-induced DNA change in structure was not a random but preferential effect. © 2009 Elsevier Inc. All rights reserved.